Review of understanding motives and ethics: the impact on civil servants' political knowledge and federal governance systems - Ahmad Aliyu, Aisha; Ismail, Mohd Mahadee; Md. Nor, Mohd Sabri (Human Resource Management Academic Research Society, 2024)
The role of civil servants in shaping governance federal systems is influenced by motives and adherence to ethical principles, which directly impact political knowledge and decisionmaking. The article examines how motives and ethics among civil servants influence governance effectiveness and public trust in federal systems. This review analyzed existing literature on the intersection of motives, ethics, and political knowledge within the context of civil service in federal systems—a systematic review methodology covering studies published between 2003 and 2023. Searches were conducted in PubMed, Scopus, Web of Science, JSTOR, and Google Scholar using relevant keywords and search strings. The inclusion and exclusion criteria were applied during the screening process, followed by data extraction and quality assessment. The findings revealed civil servants' ethical motives enhance accountability and decision-making, while challenges like political patronage and ideological bias can hinder integrity and objectivity. Specialized knowledge from policy advocacy motives may limit broader governance effectiveness. The findings emphasize the need for strong ethical frameworks, continuous training, and institutional support to promote knowledgeable and ethically driven governance. This study recommends more robust ethical training programs, clear regulatory frameworks, and enhanced oversight mechanisms to ensure that civil servants' motives align with the principles of good governance.